Comparison study of dynamic models for satellite formation flying - Hang, Yue (2009)
This thesis focuses on the comparison of dynamic models for satellite formation flying with the aid of simulation platforms Satellite Tool Kit (STK) and Matlab. One key challenge in formation flying technology is to model satellite relative dynamics. Based on the relative motion dynamic models, we can develop formation design and control strategies. Much work has been done concerning the relative motion of two satellites. In this thesis, firstly, a review is conducted on dynamic models of satellite formation flying. Then STK and Matlab will be used to evaluate the impact of different orbital perturbations on several linearized model. Later a model error index will be introduced to cornpare the accuracy of various dynamic models. Finally, the simulation results and analysis are presented.